Analysis of Genes That Encode DtxR-Like Transcriptional Regulators in Pathogenic and Saprophytic Corynebacterial Species - Oram, Diana Marra (American Society for Microbiology, 2004)
Metal-dependent transcriptional regulators of the diphtheria toxin repressor (DtxR) family have been identified in a wide variety of bacterial genera, where they control gene expression in response to one of two metal ions, Fe(2+) or Mn(2+). DtxR of Corynebacterium diphtheriae is the best characterized of these important metal-dependent regulators. The genus Corynebacterium includes many phenotypically diverse species, and the prevalence of DtxR-like regulators within the genus is unknown. We assayed chromosomal DNA from 42 different corynebacterial isolates, representing 33 different species, for the presence of a highly conserved region of the dtxR gene that encodes the DNA-binding helix-turn-helix motif and metal-binding site 1 within domains 1 and 2 of DtxR. The chromosome of all of the isolates contained this conserved region of dtxR, and DNA sequencing revealed a high level of nucleotide sequence conservation within this region in all of the corynebacterial species (ranging from 62 to 100% identity and averaging 70% identity with the dtxR prototype). The level of identity was even greater for the predicted protein sequences encoded by the dtxR-like genes, ranging from 81 to 100% identity and averaging 91% identity with DtxR. Using a DtxR-specific antiserum we confirmed the presence of a DtxR-like protein in extracts of most of the corynebacterial isolates and determined the precise amount of DtxR per cell in C. diphtheriae. The high level of identity at both DNA and protein levels suggests that all of the isolates tested encode a functional DtxR-like Fe(2+)-activated regulatory protein that can bind homologs of the DtxR operator and regulate gene expression in response to iron.